Upaya Meningkatkan Ketrampilan Sosial Anak Usia 3 - 4 Tahun Melalui Bermain Berkelompok - Sari, Etik Etika (Indonesian Journal of Islamic Early Childhood Education, 2017)
This study aims to improve childrens social skills through group-play in KB Pelangi Bina Bangsa. This research want to provide the insight and benefit to all parties involved in the world of early childhood education in the field of social skills in general, and KB Pelangi Bina Bangsa as a place of research in particular. This research used a classroom action research consisting of two cycles, each cycle consists of 4 stages, namely: planning, action implementation, observation and reflection. The subjects in this study were the students of KB Pelangi Bina Bangsa in age 3 â 4. It used observation as a method, data collection tool is observation sheet, documentation and interview. Based on the result of the research, after the action by applying group play activities, can improve the social skills of children in age 3 - 4 years in KB Pelangi Bina Bangsa. Before the action averaged 16.6% of the children in the category of complete then in the first cycle to 58% and in the second cycle increased to 91.7% of children in the category of complete.